William Penny (1809-1892) - Ross, W. Gillies (ARCTIC, 1983)
To William Penny belongs the distinction of undertaking the first maritime search for the ships of Sir John Franklin. . One of Penny's concerns was that the arctic regions north of Canada, which were ostensibly British on the basis of many discovery expeditions since Frobisher's in 1576, might fall to the United States if Britain failed to exert her authority there. [He applied for a land grant in 1852 to forestall the plans of American whaling interests to establish bases on Baffin Island. Unfortunately, this was denied.] . By expanding the frontier of the Davis Strait whale fishery, by developing the technique of wintering on board whaleships, by pointing the way into Lancaster Sound for subsequent Franklin searches, and by initiating the first missionary presence on Baffin Island, William Penny influenced the course of Euro-American activity in the eastern Arctic during the nineteenth century.